2023
DOI: 10.1021/jacs.3c00734
|View full text |Cite
|
Sign up to set email alerts
|

Water Charge Transfer Accelerates Criegee Intermediate Reaction with H2O Radical Anion at the Aqueous Interface

Abstract: Criegee intermediates (CIs) are important carbonyl oxides that may react with atmospheric trace chemicals and impact the global climate. The CI reaction with water has been widely studied and is a main channel for trapping CIs in the troposphere. Previous experimental and computational reports have largely focused on reaction kinetic processes in various CI−water reactions. The molecular-level origin of CI's interfacial reactivity at the water microdroplet surface (e.g., as found in aerosols and clouds) is unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 83 publications
2
7
0
Order By: Relevance
“…The corresponding reaction pathways have been computed with high-level quantum chemistry methods and confirmed by further experiments. , Smith et al found that this reaction is faster at a lower temperature and shows a highly negative temperature dependence . We note that a recent theoretical study has mentioned the importance of charge separation on water surfaces promoting reaction between CIs and H 2 O – radical anion …”
Section: Introductionsupporting
confidence: 54%
“…The corresponding reaction pathways have been computed with high-level quantum chemistry methods and confirmed by further experiments. , Smith et al found that this reaction is faster at a lower temperature and shows a highly negative temperature dependence . We note that a recent theoretical study has mentioned the importance of charge separation on water surfaces promoting reaction between CIs and H 2 O – radical anion …”
Section: Introductionsupporting
confidence: 54%
“…The air–water interface is another type of water–hydrophobic interface. In the recent years, water microdroplet chemistry has drawn tremendous attention for its abilities to accelerate chemical reactions by several orders of magnitude compared with the same reactions in bulk water, and to trigger spontaneous reactions that cannot occur in bulk water. It has been shown in many studies that there is a spontaneous high electric field (as high as 1.4 V/nm) at the air–water interface of microdroplets. Several studies have reported that the field originates from the formation of electric double layers, or the alignment of the free O–H bonds of the interfacial water molecules, or the partial charge transfer that resulted in the interfacial H 2 O + --H 2 O – pairs. A plethora of redox reactions can be triggered by the electric field at the air–water interface of water microdroplets, and more importantly, scalability by microdroplet chemistry becomes practical …”
mentioning
confidence: 99%
“…One way is the direct transfer of single electron from the hydroxyl anion (OH – ) to generate the hydroxyl radical (OH – → OH· + e) facilitated by the strong electric field across the AWI (10 7 V/cm). Another way involves single-electron transfer from the OH – to H + (H + + OH – → H· + OH·), which is reported as a thermodynamically favorable process in the AWI region (Δ H = −375 kJ mol –1 ) . Many spontaneous redox reactions across the AWI have been successfully observed during this process. Furthermore, the charge transfer during contact electrification between the water–solid and water–gas interfaces also contribute to the abundant presence of OH·. , With aid of the generated OH· across the AWI, organic syntheses have been readily achieved by the radical-initiated C­(sp 3 )–H activation of toluene in the water microdroplets such its C–N coupling with amines and its C–C coupling with carbon dioxide. , …”
mentioning
confidence: 91%